Familial history of stroke is associated with acute coronary syndromes in women. - Banerjee, A; Lim, C; Silver, L; Welch, S; Banning, A; Rothwell, P (2011)
BACKGROUND: Stroke in female first-degree relatives (FDRs) is a powerful risk factor for ischemic stroke in women, but its association with acute coronary syndromes (ACS) is unknown. Family history (FH) of stroke is omitted from existing myocardial infarction risk prediction tools, which perform less well in women than in men. Our objective was to study the sex-of-parent and sex-of-proband interactions for FH of stroke in ACS patients. METHODS AND RESULTS: In a prospective, population-based study (Oxford Vascular Study) of all patients with ACS or stroke/transient ischemic attack, FH data for stroke and myocardial infarction were analyzed by sex of proband and FDRs, and coronary angiograms were reviewed, where available; 942 of 1058 ACS probands and 1015 of 1152 stroke/transient ischemic attack probands had complete FH data; 24.1% of ACS probands and 24.3% of stroke/transient ischemic attack probands had history of stroke in ≥1 FDR. Maternal stroke was more common than paternal stroke in female ACS probands (odds ration [OR], 2.53; 1.39 to 4.61) but not in male probands (OR, 0.92; 0.64 to 1.32) (difference-P=0.004). Overall, female ACS probands were more likely to have female than male FDRs with stroke (OR, 2.09; 1.29 to 3.37), whereas the opposite trend was seen in male ACS probands (OR, 0.69; 0.50 to 0.97) (difference-P=0.0002). However, there was no association between parental history of stroke and disease localization or presence of multivessel disease on coronary angiography. CONCLUSIONS: FH of stroke is as common in ACS patients as in stroke/transient ischemic attack patients and sex-of-parent/sex-of-proband interactions are similar. Stroke in female FDRs may help to identify women at increased risk of ACS as well as ischemic stroke.